Effect of Liming of Tea Seedling (Camellia sinensis (L.)O. Kuntze) - FATEMI CHOKAMI, ALI; AZADI GONBAD, REZA (Asian Journal of Chemistry, 2010)
For determination of soil pH in tea seedling a pot experiment was conducted in sandy loom soils in Shahid Islami tea research station of Lahijan. The soils with pH = 3.5 was collected from Gasht in Fuman and mixed with different doses of calcium carbonate to reach the soil pH to T1 = 3.5, T2 = 4, T3 = 4.5, T4 = 5, T5 = 5.5, T6 = 6 base on Foths formula. After 7 months, the soil pH was stabilized and clone 100 was planted in this pots the experiment was conduct in completely randomized block design with 6 treatment and three replications each treatment in each replication consists of two pots with 10 kg of soil. After 7 month the growth parameters such as shoot height, root length and whole plant weight were measured. The result showed that soil pH was not significant on the shoot length and wet weight. But reaction of shoot height in T3 (pH = 4.5) and wet weight in T2 (pH = 4) was more. All treatments in root length was also significant at p = 0.05 with Duncan method and T2, T3, T4 were in first class and T5 and T6 was in second class.